HYDROALLANTOIS IN A SHE BUFFALO - SELVARAJU, M; MANOKARAN, S; PALANISAMY, M; NAPOLEAN, R EZAKIAL; RAVIKUMAR, K (The Indian Journal of Animal Reproduction, 2023)
A successful management of hydrallantois in a non-descript buffalo is reported.